An assessment of improving the sustainable agro-touristic offer in an emerging country using the integrative approach based on fuzzy logic - Puška, Adis; Nedeljković, Miroslav; Jeločnik, Marko; Subić, Jonel; Nancu, Dumitru; Andrei, Jean Vasile (Frontiers in Environmental Science, 2022)
The process of improving tourism requires prior determination of the existing offer, as well as assessment of the advantages and weaknesses of the given offer. Upon the analysis, it is possible to improve the tourist offer. This paper examined ways in which agro-tourism can be improved, related to the foundation of sustainability. Methodologically, paper involves the use of expert assessment, additionally supported with fuzzy logic based on the fuzzy PIPRECIA and fuzzy MARCOS methods. Using the fuzzy PIPRECIA method, the criteria and sub-criteria were weighted, while the observed agro-tourism facilities in Bosnia and Herzegovina (BiH) were ranked according to applied fuzzy MARCOS method. Out of the six facilities in question, the most ap-propriate results are achieved at the "Šadrvan" rural household, while the worst outcome is exhibited at the agro-tourism facility (rural household) „Kovačević“. The obtained results were confirmed as well by the sensitivity analysis. The aim of the paper was not only to rank agro-tourism facilities, but to determine their advantages and disadvantages as function of improving the complete agro-tourism in BiH. Based on the obtained results, the facilities management should determine which sustainability criteria would need to be improved, as well as on which criteria it is desirable to build a competitive advantage aiming to advance the tourist offer. In the future research, it is important to include more agro-tourism facilities in order to obtain complete information on the current state of agro-tourism in BiH